IMPACT OF GLOBAL SUPPLY CHAIN DISRUPTIONS ON BUSINESS PERFORMANCE OF DANGOTE CEMENT PLC, OBAJANA (ABUJA JOURNAL OF BUSINESS AND MANAGEMENT, 2025)
This study investigated the impact of Global Supply Chain Disruptions on Business Performance of Dangote Cement Plc, Obajana, focusing on exchange rate fluctuations influence business performance. A descriptive research design was employed, utilizing stratified sampling to collect data from the respondents. Questionnaires were distributed to employees of Dangote Cement Plc, with a total population of 2,428. Stratified and simple random sampling techniques were applied within each stratum, and a sample size of 343 was determined, with an additional 20% margin of safety. The data were analyzed using inferential statistics and regression analysis, with a 5% level of significance to test the hypotheses aligned with the study's objectives. The findings revealed that exchange rate fluctuations have a significant effect on the product pricing of Dangote Cement Plc in Obajana. The study concluded that exchange rate fluctuations have a significant effect on the product pricing of Dangote Cement Plc in Obajana. It recommended that Management of Dangote plc should conduct regular market analysis and monitoring of exchange rate trends will enable the company to make informed decisions regarding pricing adjustments. This proactive approach can help anticipate potential cost impacts and allow for timely responses.